FOLK GAMES-AN IMPORTANT FACTOR IN THE UPBRINGING OF THE PERFECT GENERATION - Raxmonova Maxfuza Xolmurodovna (American Journals Publishing, 2023)
The article examines the origin factors and types of national folk games and talks about their importance in raising a healthy generation. Pedagogical recommendations are given regarding the use of folk games in educational processes.
Keywords: Intangible cultural heritage, national folk games, national traditions and values, healthy generation, education and upbringing, healthy lifestyle, modern pedagogical technologies.